Analisis Pengendalian Persediaan Bahan Baku dengan Metode Min-Max Stock Pada PT Berkah Anugerah Inti Semesta - Bagaskara, Tegar Winoto; Safirin, Moch. Tutuk (Jurnal Serambi Engineering, 2025)
This study analyses the management of raw material inventory at PT Berkah Anugerah Inti Semesta using the Min-Max Stock method. This study aims to identify problems in inventory control that often result in overstocking and understocking, which affects operational efficiency and storage costs. The research methods include observation and interviews to collect data on the use and purchase of raw materials over a period of time. The results showed that the application of the Min-Max Stock method was able to reduce the risk of raw material shortages and significantly reduce storage costs. The determination of safety stock, minimum and maximum stock levels provides companies with clear guidance on how to maintain stock levels. These findings confirm the importance of an efficient inventory management strategy to improve smooth production and the company's competitiveness in the market. This research is expected to be a reference for other companies facing similar challenges, providing insights into effective inventory control practices.